(untitled) (International Journal of Communication Systems and Network Technologies, 2024)
This paper presents the comprehensive design, fabrication, and experimental implementation of an innovative Automated Trimmer System (ATS). The increasing demand for efficiency and precision in various industries has prompted the development of automated solutions, and trimming processes are no exception. The ATS detailed in this research integrates cutting-edge design principles and advanced fabrication techniques to address existing challenges in conventional trimming systems.The design phase elucidates the system architecture, emphasizing the selection of materials, sensors, and components crucial for optimal functionality. A step-by-step fabrication process is outlined, detailing the manufacturing of the ATS with a focus on overcoming challenges encountered during the construction. The resulting system is a robust and versatile solution poised to enhance trimming processes across diverse applications.In the experimental phase, the ATS is subjected to a rigorous testing regimen to evaluate its performance under various conditions. Quantitative data, supported by graphical representations, showcase the system’s efficiency, precision, and adaptability. The results reveal promising outcomes and demonstrate the ATS’s potential to revolutionize trimming operations in terms of speed, accuracy, and resource utilization. Limitations of the study are addressed, and future research directions are suggested to further refine and expand the capabilities of the ATS.In conclusion, this research contributes a significant advancement to the field of automated trimming systems, presenting a meticulously designed, fabricated, and experimentally validated ATS. The innovative features of the system hold promise for widespread applications, marking a substantial step forward in the pursuit of enhanced efficiency and precision in industrial trimming processes.